2011
DOI: 10.1007/s12645-011-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liposomal celecoxib on proliferation of colon cancer cell and inhibition of DMBA-induced tumor in rat model

Abstract: Celecoxib, a selective cyclooxygenase-2 inhibitor, has shown potential anticancerous activity against majority of solid tumors especially on patients with colon cancer. However, associations of serious side effects limit the usage of celecoxib in colon cancer treatment. To address this issue and provide an alternative strategy to increase the efficacy of celecoxib, liposomal formulation of celecoxib was prepared and characterized. Anticancer activity of liposomal celecoxib on colon cancer cell HCT 15 was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In the current study, the percentage of CLX incorporation to the cholesterol‐containing LUVs was greater than 70%. A recent study reported a 46% of entrapment efficiency for cholesterol‐free CLX‐loaded liposomes (DSPC only) prepared by sonication instead of extrusion . An immunoliposomal formulation containing CLX targeted to vascular cell adhesion molecule‐1 was prepared with 1,2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine, cholesterol, and 1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐ n ‐(glutaryl) in 65:25:10 or 70:25:5 mol % by sonication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the percentage of CLX incorporation to the cholesterol‐containing LUVs was greater than 70%. A recent study reported a 46% of entrapment efficiency for cholesterol‐free CLX‐loaded liposomes (DSPC only) prepared by sonication instead of extrusion . An immunoliposomal formulation containing CLX targeted to vascular cell adhesion molecule‐1 was prepared with 1,2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine, cholesterol, and 1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐ n ‐(glutaryl) in 65:25:10 or 70:25:5 mol % by sonication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a 46% of entrapment efficiency for cholesterol-free CLX-loaded liposomes (DSPC only) prepared by sonication instead of extrusion. 29 An immunoliposomal formulation containing CLX targeted to vascular cell adhesion molecule-1 was prepared with 1,2-dimyristoyl-sn-glycero-3phosphocholine, cholesterol, and 1,2-dipalmitoyl-sn-glycero-3phosphoethanolamine-N-(glutaryl) in 65:25:10 or 70:25:5 mol % by sonication. This preparation was reported to result in 208 -308 :g/mL CLX that corresponds to 2.7%-3% loading.…”
Section: Discussionmentioning
confidence: 99%
“…MTT-assay for MCF-7 and MBA-MB-231 cytotoxicity was used, as before 29 30 . Briefly, 100 μl of 2 × 10 3 cells were seeded into each well of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Small molecule inhibitors have advantages over larger molecules, such as monoclonal antibodies. These advantages include easy diffusion across the cell membrane, which facilitates large-scale experiments in which there might be difficulties in transfection or knockdown using RNAi (Gowda, Jones, Banerjee, & Robertson, 2013; Madani, Naderi, Dissanayake, Tan, & Seifalian, 2011; Parhi, Mohanty, & Sahoo, 2012; Perumal, Banerjee, Das, Sen, & Mandal, 2011). Small molecule inhibitors can be administered orally, whereas biologics generally require injection or another parenteral administration.…”
Section: Anticancer Therapeutics and Nanoparticle-based Delivery Agentsmentioning
confidence: 99%